Household air pollution exposure and respiratory health outcomes: a narrative review update of the South African epidemiological evidence - Shezi, Busisiwe; Wright, Caradee Y (Clean Air Journal, 2018)
One of the greatest threats to public health is personal exposure to air pollution from indoor sources. The impact of air pollution on mortality and morbidity globally and in South Africa is large and places a burden on healthcare systems for treatment and care of air pollution-related diseases. Household air pollution (HAP) exposure attributed to the burning of solid fuels for cooking and heating is associated with several adverse health impacts including impacts on the respiratory system. The researchers sought to update the South African evidence on HAP exposure and respiratory health outcomes from 2005. Our quasi-systematic review produced 27 eligible studies, however, only four of these studies considered measures of both HAP exposure and respiratory health outcomes. While all of the studies that were reviewed show evidence of the serious problem of HAP and possible association with negative health outcomes in South Africa, no studies provided critically important information for South Africa, namely, local estimates of relative risks that may be applied in burden of disease studies and concentration response functions for criteria pollutants. Almost all of the studies that were reviewed were cross-sectional, observational studies. To strengthen the evidence of HAP exposure-health outcome impacts on respiratory health, researchers need to pursue studies such as cohort, time-series and randomised intervention trials, among other study designs. South African and other researchers working in this field need to work together and take a leap towards a new era of epidemiological research that uses more sophisticated methods and analyses to provide the best possible evidence. This evidence may then be used with greater confidence to motivate for policy-making, contribute to international processes such as for guideline development, and ultimately strengthen the evidence for design of interventions that will reduce HAP and the burden of disease associated with exposure to HAP in South Africa.